1999
DOI: 10.1046/j.1365-2885.1999.00209.x
|View full text |Cite
|
Sign up to set email alerts
|

Enantiospecific pharmacokinetics and pharmacodynamics of ketoprofen in sheep

Abstract: Pharmacokinetic and pharmacodynamic parameters were established for the enantiomers of the 2-arylpropionic acid (APA) nonsteroidal anti-inflammatory drug (NSAID), ketoprofen (KTP). Each enantiomer was administered separately (1.5 mg/kg) and in a racemic mixture (3 mg/kg) intravenously (i.v.) to a group of eight sheep in a four-way, four-period cross-over study using a tissue cage model of inflammation. Plasma disposition of each KTP enantiomer was similar following separate administration of the pure compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
38
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 52 publications
6
38
1
Order By: Relevance
“…The elimination half-life of ketoprofen in plasma was higher after the overdose of ketoprofen in the sheep of the present study than in sheep in other studies 25,26 after administration of a frequently used dose of racemic ketoprofen (3 mg/kg) or its enantiomers. Approximately 2 hours after administration of ketoprofen at a dose of 30 mg/kg, the plasma concentration of ketoprofen in our study was at the same value as the maximum concentration reported in sheep after administration at the frequently used dose of 3 mg/kg.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…The elimination half-life of ketoprofen in plasma was higher after the overdose of ketoprofen in the sheep of the present study than in sheep in other studies 25,26 after administration of a frequently used dose of racemic ketoprofen (3 mg/kg) or its enantiomers. Approximately 2 hours after administration of ketoprofen at a dose of 30 mg/kg, the plasma concentration of ketoprofen in our study was at the same value as the maximum concentration reported in sheep after administration at the frequently used dose of 3 mg/kg.…”
Section: Discussioncontrasting
confidence: 66%
“…Approximately 2 hours after administration of ketoprofen at a dose of 30 mg/kg, the plasma concentration of ketoprofen in our study was at the same value as the maximum concentration reported in sheep after administration at the frequently used dose of 3 mg/kg. 25,26 Thus, exposure to the toxic plasma concentration of ketoprofen was probably relatively short, and most of the injuries in the tubular cells can be expected to have taken place during the early phase of our follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…32 The concentration of ketoprofen in plasma was 4.5-8.4 μg/mL in our sheep at 2 h after administration and R-ketoprofen has been recorded as the most prominent enantiomer found in sheep. 17 Based on these results, oral administration of the three NSAIDs at twice the standard parental dose shown to be therapeutic in other species was expected to be still within the therapeutic range for sheep; however, it is recommended that work should be done to identify the therapeutic levels in sheep.…”
Section: Discussionmentioning
confidence: 99%
“…There were four treatment groups: carprofen (8.0 mg/kg, PiaPharma, NSW, Aust), ketoprofen (8.0 mg/kg, PiaPharma), flunixin (4.0 mg/kg, PiaPharma) and saline (Baxter, NSW, Aust) daily for the 6 days of the trial. Dose rates were based on doses of these NSAIDs given to sheep in previous experiments, 16,17 but doubled because of the rumen's potential to reduce bioavailability. All the treatment groups were given their assigned treatment orally as a solution by syringe to the back of the tongue.…”
Section: Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation